Notas geomorfológicas acerca del Foco endorréico en la margen izquierda del río Duero, aguas abajo de Soria - Echeverría Arnedo, María Teresa (Geographicalia, 2017)
Localization of an endorheic focus in the left bank of the Duero river, downstream Soria, can be related with several factors such as lithologic, structural and climatic. The sluggish morphogenetic activify over un almost-plain surface since Pliocene times of river Duero’s fluvialnetwork, contributed to the presence of dificult drainage areas with a present-day functionalify.